2010
DOI: 10.5194/acp-10-7697-2010
|View full text |Cite
|
Sign up to set email alerts
|

Options to accelerate ozone recovery: ozone and climate benefits

Abstract: Abstract. Hypothetical reductions in future emissions of ozone-depleting substances (ODSs) and N 2 O are evaluated in terms of effects on equivalent effective stratospheric chlorine (EESC), globally-averaged total column ozone, and radiative forcing through 2100. Due to the established success of the Montreal Protocol, these actions can have only a fraction of the impact on ozone depletion that regulations already in force have had. If all anthropogenic ODS and N 2 O emissions were halted beginning in 2011, oz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…2a and b), and the largest decrease of ozone in the middle and upper stratosphere appears in the Arctic region. The result here is consistent with previous studies (Ravishankara et al, 2009;Daniel et al, 2010), which indicated that N 2 O has a large contribution to ozone depletion just above the region where ozone concentrations are largest (around 10 hPa).…”
Section: Ozone Responses To N 2 O Changessupporting
confidence: 83%
“…2a and b), and the largest decrease of ozone in the middle and upper stratosphere appears in the Arctic region. The result here is consistent with previous studies (Ravishankara et al, 2009;Daniel et al, 2010), which indicated that N 2 O has a large contribution to ozone depletion just above the region where ozone concentrations are largest (around 10 hPa).…”
Section: Ozone Responses To N 2 O Changessupporting
confidence: 83%
“…A comparison of the effect of eliminating the individual halocarbons (and anthropogenic methyl bromide and carbon tetrachloride) is shown in figure 7 [28]. This highlights the much larger potential for reducing future ozone depletion by anthropogenic N 2 O reductions compared with the elimination of emissions of any of the individual halocarbons, including the banks (i.e.…”
Section: Ozone-depletion Potentialsmentioning
confidence: 96%
“…global warming, ocean acidification, sea level rise, and so on). Figure 6 shows the evolution of global ozone changes relative to 1950 owing to the full A1B/A1 scenario and the effect of eliminating halocarbon ODS and anthropogenic N 2 O emissions after 2010 [28]. While eliminating halocarbon ODS emissions causes ozone increases in the 2010 -2060 time period, their influences are small by 2100 as the halocarbons decay to near natural levels by that time even with only the current controls.…”
Section: Ozone-depletion Potentialsmentioning
confidence: 99%
“…Considering together future projections of CO 2 , CH 4 , and N 2 O increases and ODS decreases, it is estimated that the ozone layer should eventually return to its pre-1980 levels, despite continued emissions of N 2 O and other ODSs (17). However, the Parties to the Montreal Protocol continue to consider and pursue ways to accelerate ozone recovery, such as the destruction of ODS banks and the accelerated hydrochlorofluorocarbon phase out, partly because these actions would deliver both ozone and climate benefits (18).…”
mentioning
confidence: 99%